Rhizopus Rot Controlwith Calcium Nitrate in Dioscorea Rotundata Var. Apepe - Osijo, T. A.; Otusanya, M. O.; Enikuomehin, O. A.; Afolabi, C. G.; Olowokere, F. A. (European Journal of Applied Sciences, 2022)
This study investigated the response of Dioscorea rotundata variety Apepe to tuber rot by Rhizopus stolonifer with Calcium nitrate foliar spray. The experiment was a randomized complete block (RCBD) with three replications. In the pre-planting soil analysis, Calcium, Magnesium and Potassium were 31.58cmol kg-1, 2.34cmol kg-1and 0.52cmol kg-1 respectively in the soil of the experimental site, higher than the criticals reported for the three elements for optimum production of yam in South West Nigeria. However, Nitrogen and Phosphorus were 1.06% and 11.79ppm respectively, below the criticals. Calcium nitrate at 0mgl-1, 750mgl-1, and 12000mgl-1 was sprayed 16 weeks after planting (16WAP), and then four weekly until 28WAP. Tubers inoculated at 32WAP with R. stolonifer for four weeks, had weight loss not significantly different across the three treatments. It was 0.26% for the control, 1.23% for the 750mg l-1 treatment and 5.50% for the 12000mgl-1 treatment. Infection in the 750 mgl-1 treatment was 2.26% significantly lower than the control which was 6.66%. The 750mgl-1 treatment was lower than the control by 66%. But infection in the 12000mgl-1 treatment was 60.29%, higher than the control and is thus not suitable for the control of R. stolonifer tuber rot. However, 750mgl-1calcium nitrate foliar spray is recommended for control of R. stolonifer tuber rot in variety Apepe. Tuber yield at 32WAP was the equivalent of 35.80tonsha-1, 32.50tonsha-1 and 31.10tonsha-1 in the 0mg-1, 750mgl-1 and 12000mg-1treatments respectively. Overall mean yield of 33.13tons ha-1is similar to the optimum of 34.20tons ha-1reported for economic production of yam in South West Nigeria.